Pyogenic Granuloma of Cymba Concha - unusual site of a benign lesion - Carneiro,José Pedro (2024)
Abstract Pyogenic granuloma is a benign lesion of the skin or mucosa that frequently occurs in the head and neck region. The description of this lesion in the auricle or other regions of the external ear is very rare, with 7 cases published in the literature in the last 20 years. Treatment consists of surgical excision of the lesion. We present the case of a 20-year-old woman who presented with a friable lesion of the auricle, in the region of the cymba concha. It was excised under local anesthesia. One week after excision of the lesion, she had a small scab at the excision site. Six months after excision of the lesion, it showed no signs of recurrence or visible aesthetic defects.